Jobcenters' strategies to promoting the inclusion of immigrant and native job seekers: A comparative analysis based on PASS survey data - René Lehweß-Litzmann; Janina Söhn (Journal for Labour Market Research, 2022)
This paper comparatively analyzes strategies of German Jobcenters to bring native and immigrant job seekers into employment. It focuses on clients who receive means-tested basic income for the unemployed, based on data from the Panel Study Labour Market and Social Security (PASS) from year 2015 to 2020. By way of logistic regression, the study identifies the impact of being an immigrant on the clients' probability of reporting different kinds of offers like job referrals or courses, controlling for a number of other influential factors. The study also looks deeper into the effects of immigrant-specific attributes, such as heterogeneous German language skills. We found that the likelihood of offers by Jobcenters largely depends on the amount of time since immigration. Recent immigrants have the lowest chance of reporting most of the studied measures of active labor market policies. For immigrants having stayed more than 4~years in Germany, however, we do not find a disadvantage, and some measures out of Jobcenters' toolbox are even more often offered to the longer-settled immigrants than to native clients. A possible explanation for the moderately under-average support of recent immigrants in terms of Jobcenters' measures could be an institutional focus on improving German language skills prior to approaching the labor market.
Keywords: H41; I38; J08; J15; J61; J68; 330; Active labor market policy; ALMP; Immigration; Integration; Jobcenter; Labor market; Public employment services; Training; Welfare state